Análise numérica e experimental do processo de vazamento de aço líquido da panela de aço para distribuidores no processo de lingotamento contínuo - Bruno Augusto Batista Ribeiro (2014)
The steelmaking industry is constantly searching for better production practices that will lead to improved qualities of the final product and an enhanced yield, so better operational practices are constantly been implemented. The rational use of raw materials, energy and the avoidance of waste in the industrial process lead to an effective production process. Minimization of product leftover is quite a relevant point. In the continuous casting process, large amounts of molten steel are left in the ladle during teeming as an established practice to avoid slag carry over to the Tundish, in the end of the teeming process. In the ladle a thin layer slag that is made of calcium, aluminum and magnesium oxides is used to protect the molten steel from the atmospheric air and to provide thermal insulation for the molten bath. If these oxides reach the final product they will cluster in inclusions that will cause a series of defects on the finished product. So an effective teeming process is that one that reduces the amount of slag carry over to the tundish. In order to have an cost effective process steelmakers need to transfer the largest amount of molten steel to the tundish without allowing slag carryover. Thus, the objective of this work was to experimentally and numerically analyze the flow behavior of molten steel during the ladle teeming process and the formation of any vortex like structure during the process. The numerical model obtained from this work was able to reproduce the tests that were carried out in the laboratory. The experiments showed that for an isothermal situation a drain sink would form above the nozzle when the water/kerosene was at 3 cm above the ladle bottom. This behavior was reproduced by the numerical model.